Regional Metastatic Behavior of Nonfunctional Pancreatic Neuroendocrine Tumors: Impact of Lymph Node Positivity on Survival. Issue 7 (August 2017) - Jutric, Zeljka; Grendar, Jan; Hoen, Helena M.; Cho, Sung W.; Cassera, Maria A.; Newell, Pippa H.; Hammill, Chet W.; Hansen, Paul D.; Wolf, Ronald F.
Abstract : Objectives: Literature addressing the significance of lymph node positivity in the management of nonfunctional pancreatic neuroendocrine tumors (PNETs) is conflicting. Methods: The National Cancer Data Base was queried for patients who underwent surgical resection of nonfunctional PNETs between 1998 and 2011. Clinical data and overall survival were analyzed using χ 2 and Cox proportional hazards regression. Multiple imputation was used as a comparative analysis because of the high number of patients missing data on tumor grade. Results: Two thousand seven hundred thirty-five patients were identified. The overall incidence of lymph node metastasis was 51%. In the subset of patients with grade 1 tumors less than 1 cm, 24% had positive lymph nodes. Overall median survival for patients with negative lymph nodes was 11 years compared with 8 years for lymph node–positive patients ( P < 0.001). On multivariate survival analysis, tumor grade, distant metastases, regional lymph node involvement, positive surgical margins, male sex, and older age were predictive of decreased overall survival. Conclusions: Lymph node positivity was associated with decreased overall survival. The incidence of lymph node involvement in resected low-grade tumors less than 1 cm is higher than previously reported. Patients selected for resection of PNETs should be offered lymphadenectomy for staging.